Increased Knowledge Through Psychological Adaptation Education for Postpartum Mothers in The Work Area of Antang Perumnas Public Health Center - Firawati, Firawati; Hasnaeni; Purnamasari, Lili (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
During the postpartum period, the ability to adjust is very important, less than optimal adjustments can cause the mother to experience various problems such as postpartum blues, postpartum depression, postpartum psychosis. The mother's reaction after giving birth will affect her attitude, behavior, and emotional level. Psychological stress after childbirth is an emotional and emotional symptom, where a person feels moody, can't sleep, is excessively physically exhausted, and doesn't know what to do with his new role. The purpose of this community service is to empower the community for cadres and postpartum mothers in increasing knowledge about preventing psychological problems in postpartum mothers. The method of implementing this service activity is to use a model of increasing partnerships with health cadres and postpartum mothers by providing health promotion education about preventing psychological problems and postnatal health screening. This activity was carried out in May 2022 with 23 participants participating. The results of Community Service showed that before the extension, the majority of respondents had sufficient knowledge of 48% and the minority had good knowledge of 39%. While the results of the evaluation of activities after being given counseling on psychological adaptation of postpartum mothers, the majority of respondents had good knowledge of 78% and the minority had sufficient knowledge of 13%. Conclusion There is an increase in knowledge about the psychological adaptation of postpartum mothers. This community empowerment activity can be used as health promotion regarding the prevention of postpartum psychological problems as an effort to improve maternal health after childbirth.